ORGANIZAÇÃO E DESENVOLVIMENTO HUMANO: UM ESTÍMULO PARA EVENTOS ESCOLARES - Mosmann, Vera Maria (Revista Liberato, 2013)
This work aims propose a social and systemic view about institutional administration under scientifically vision, involving the aspects of the human organizations, the sensibility aesthetic and the structure events organization. In this point of view an event with international characteristics called 8º SIET was created - SEMINARIO INTERNACIONAL DE EDUCAÇÃO TECNOLÓGICA, together with the 16ª MOSTRATEC - Mostra Internacional de Tecnologia. The management’s event above work focused in some moments to discussing e reflecting the questions about education and technology with a scientifically vision, creating opportunities to live feelings moments, waking up affectivity feelings and solidarity. As result of that, this sentimentalism motivated the space’s creation for artistically and cultutral production, helping touch the people in search of the enterprising, happiness, became them self agent history. The link between humanistic and technician area can be the way to turn on the management’s educational into a global and systemic approach.